2010
DOI: 10.1002/smll.201001476
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Temperature and Size of Hot Spots and Hot‐Spot Arrays

Abstract: By using scanning thermal microscopy, it is shown that nanoscale constrictions in metallic microwires deposited on an oxidized silicon substrate can be tuned in terms of temperature and confinement size. High-resolution temperature maps indeed show that submicrometer hot spots and hot-spot arrays are obtained when the SiO(2) layer thickness decreases below 100 nm. When the SiO(2) thickness becomes larger, heat is less confined in the vicinity of the constrictions and laterally spreads all along the microwire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…200 A number of developments based on new cantilevers and new AFM-based temperature measuring techniques have been stated in recent years. 43,45,[201][202][203][204][205][206][207][208][209][210] Sadat et al 23 have reported a thermometric AFM-based technique which does not require integrated temperature sensors in AFM probes. The technique allows direct mapping of topography and temperature fields of metal surfaces with $0.01 degree temperature resolution and <100 nm spatial resolution.…”
Section: Scanning Thermal Microscopymentioning
confidence: 99%
“…200 A number of developments based on new cantilevers and new AFM-based temperature measuring techniques have been stated in recent years. 43,45,[201][202][203][204][205][206][207][208][209][210] Sadat et al 23 have reported a thermometric AFM-based technique which does not require integrated temperature sensors in AFM probes. The technique allows direct mapping of topography and temperature fields of metal surfaces with $0.01 degree temperature resolution and <100 nm spatial resolution.…”
Section: Scanning Thermal Microscopymentioning
confidence: 99%
“…The use of a scanning thermal microscope (SThM) adapted for fluorescence reads (Benayas et al, 2012) was reported by Aigouy et al (2005, 2009, 2011) and Saïdi et al (2009, 2011) to work in the sub-wavelength spatial resolution regime. Regarding high-resolution thermal imaging of integrated circuits, Saïdi et al (2011) used a small fluorescent Er 3+ /Yb 3+ -doped PbF 2 nanocrystal as a temperature sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding high-resolution thermal imaging of integrated circuits, Saïdi et al (2011) used a small fluorescent Er 3+ /Yb 3+ -doped PbF 2 nanocrystal as a temperature sensor. The technique presents temperature uncertainly ~1.0 K, spatial resolution of 0.027 μm, despite the relatively long acquisition times (100 ms per pixel), that invalidates the transient mapping of the device (Saïdi et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] It is required in many fields, ranging from integrated photonics (where the unavoidable light-induced thermal loading could lead to a drastic deterioration in the performance of active optical circuits) to micro/nano electronics (where the appearance of Joule-induced "hot-spots" is one of the most common causes of fatal failure). 5,6 This can be extended to the case of the new generation opto-fluidic devices which nowadays constitute lab-on-a-chip platforms with numerous applications in life sciences, such as cell manipulation and sorting. 7,8 In these applications, light is used to manipulate living cells that propagate within micro-fluidics through the use of optical forces.…”
Section: Introductionmentioning
confidence: 99%